Logística reversa de medicamentos vencidos e em desuso no município de João Pessoa/PB - Toscano, Ianina Gonzalez (2019)
Waste medicines are commonly discarded improperly in toilets and sinks and or as household waste, which cause risk to the environment and public health. Proper solid waste management enables to minimize the production and provide appropriate final disposal. The aim of the study was to analyze the reverse logistics of collection and disposal of expired and disused medicines in the city of João Pessoa, in order to verify the population's access and effectiveness. The study was developed from a sample of the municipality's pharmacy and drugstore register and the application of a checklist in pharmaceutical establishments in the five specific poles defined in the Municipal Solid Waste Management Plan and an interview with the responsible for the medicines sector in Municipal Sanitary Surveillance. The results show that most of pharmacies and drugstores in the city of João Pessoa interviewed have solid waste management plan (98,54%) and or practice the reverse logistics of expired and disused medicines (95.1%). The 5th Pole was the area that stood out because it has the lowest literacy and income index and the one that most applies the criteria of reverse logistics practice. The lack of information available to the public about the proper disposal of medications and noncompliance to the laws that deal with specifications for the practice of reverse logistics has been verified. This research could assist in making decisions on reverse logistics and expired medications into disuse in the legislative and operational framework, based on the results of the practice carried out in pharmaceutical establishments in the city of João Pessoa.